The educational and social value of university orchestras - Lorenzo de Reizábal, Arantza (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The aim of this research is to determine the different training and social transfer contributions of university orchestras, based on the evaluations made by the participants in this musical activity. The methodological approach applied is quantitative and uses the questionnaire as a data collection technique. The results indicate that university orchestras have a great formative value that transcends the musical educational field, since their positive impact also encompasses the different dimensions of the human being and permeates society. It is concluded that it is necessary to maintain and promote this type of orchestral ensembles.